Manajemen Retensi dalam Upaya Mempertahankan Karyawan melalui Dorongan Kepuasan dan Komitmen - SULISTYAN, RIZA BAHTIAR; Ermawati, Emmy; Yunus Ariyono, Kurniawan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2019)
Special attention needs to be paid by the company regarding the employee's intention to leave the organization. The purpose of this study is to develop a conceptual model to prove empirically how retention management can encourage job satisfaction and commitment so that employees do not intend to leave the organization. As many as 36 account officers in Lumajang Regency are willing to become respondents. The approach used is PLS. The results showed that retention management and employee satisfaction were directly able to reduce employee intentions to leave the organization. Employee commitment has not been able to reduce the intention of employees to leave the organization. It is more important to improve the management of employee retention and job satisfaction than their commitment as an effort to minimize the intention of employees leaving the organization.